EFFICIENCY OF PRODUCTION OF HORSE MEAT AND KOUMISS FROM THE KAZAKH HORSES OF THE ADAI OFFSPRING - Kargaeyeva Makpal (Academic Journal of Physical and Chemical Sciences, 2020)
Kazakh horses of the Adai offspring are the standard of herd horses in the desert zone of the Mangyshlak Peninsula. They perfectly adapt to the area of their reproduction, hardy to long-distance driving to various pastures. With an insignificant expenditure of labor and money, young Adai horses reach 340-350 kg of live weight by the age of 2.5 years. When slaughtering stallions, the carcass weight reaches 185-195 kg. High-milk mares for 105 days of lactation produce from 590 liters to 675 liters of marketable milk. The rates of slaughter yield in Adai young stock were also comparatively lower than that of stallions of the Mangystau population and averaged to 53.9 %, while the rate of slaughter yield in horses of the Mangistau population was 55.1 %. When studying the dairy productivity of both groups of mares, it was found that mares of the Adai offspring have higher dairy productivity than the Mangistau population under pasture conditions. Over 105 days of lactation, the milking capacity of the mares of the Adai offspring was 1617.0 liters, in the Mangistau population it was 1413.3 liters, and commercial milk yield was 674.1 and 590.1 liters, respectively. Thus, the yield of the Adai mares exceeds by 14.2 % or 84.0 liters in comparison with the Mangistau population. Profitability in the horse meat production reaches from 70 % to 74 % and in koumiss production – 13.9-16.9 %.